PENGARUH RETURN ON ASSET DAN INTANGIBLE ASSET TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL PEMODERASI - widhiastuti, Ni Luh Putu; Latrini, Made Yenni (E-Jurnal Akuntansi, 2015)
Th is study aims to determine the influence of  return on assets and intangible assets on corporate value with corporate social responsibility as a moderating variable. Using 29 companies in banking industry in Indonesia Stock Exchange during 2010-2013 with probability sampling methods. Data was collected through nonbehavioral observation. Data are analyszed us ing multiple linear regression and moderation analysis regression. Results of statistical t test showed (1) increasing return on asset will increase corporate value, (2) increasing intangible asset will increase corporate value, (3) the disclosure of corporate social responsibility is able to moderate relation of  return on asset and corporate value, (4) the disclosure of corporate social responsibility is unable to moderate relation of  return on asset and corporate value.
Keywords: return on asset, intangible asset, corporate value, corporate social responsibility